고주파 전기수술기를 이용한 각막 신생혈관의 치료 2예 - 최영주(Young Joo Choi); 한겨레(Gyu Le Han); 정태영(Tae Young Chung); 임동희(Dong Hui Lim) (Daihan angwa haghoi jabji, 2021)
목적: 약물치료와 레이저광응고술 후 재발한 각막 신생혈관에서 고주파 전기수술기를 이용한 치료를 보고하고자 한다. 증례요약: (증례 1) 53세 남자 환자가 우안 각막혼탁을 주소로 내원하였다. 교정시력은 0.6이었다. 각막 하측에 신생혈관을 동반한 지질각막병증이 관찰되었다. 약물치료와 레이저광응고술에도 각막혼탁은 큰 변화가 없었으며 공급혈관의 재발이 관찰되었다. 이에 고주파 전기수술기를 이용해 신생혈관 소작을 시행하였다. 1개월 후 교정시력은 0.9로 호전되었으며, 이후 4년 동안 신생혈관은 재발하지 않았고 각막혼탁도 서서히 줄어들었다. (증례 2) 23세 여자 환자가 1주 전부터 발생한 좌안 통증을 주소로 내원하였다. 각막 신생혈관에 대해 레이저광응고술을 3차례 받았던 환자였다. 내원 당시 좌안 나안시력은 0.4로 측정되었다. 각막 상측에 신생혈관의 재발이 관찰되어 신생혈관 소작을 시행하였다. 치료 2개월 후 신생혈관 재발 없이 각막혼탁은 감소하였으며 나안시력은 0.5로 호전되었다. 결론: 각막 신생혈관 환자에서 고주파 전기수술기는 쉽고 효과적이며, 합병증 없이 각막혼탁의 감소 및 시력호전을 유도할 수 있다. Purpose: To report two cases of treatment using high-frequency radio wave electrosurgery for corneal neovascularization that recurred after medication and laser photocoagulation attempts. Case summary: (Case 1) A 53-year-old man visited our hospital complaining of corneal opacity. The best-corrected visual acuity in the left eye was 0.6. Lipid keratopathy indicated new inferior vessels. There was no significant change in corneal opacity after medication and laser photocoagulation; however, the recurrence of feeder vessels was observed. Therefore, electrocautery was performed via high-frequency radio wave electrosurgery. Visual acuity, measured 1 month later, improved to 0.9. Over the subsequent 4-year observation period, new vessels did not recur and the corneal opacity decreased gradually. (Case 2) A 23-year-old woman visited complaining of left eye pain. She had undergone laser photocoagulation three times for corneal new vessels. Visual acuity in her left eye was 0.4. Recurrence of new vessels at the upper cornea was observed, and electrocautery was performed. After 2 months, corneal opacity decreased without revascularization, and visual acuity improved to 0.5. Conclusions: In patients with corneal neovascularization, electrocautery using high-frequency radio wave electrosurgery is simple and effective and can reduce corneal opacity and improve vision without complications. KCI Citation Count: 0